ANALISIS KESESUAIAN PROGRAM JAMINAN KESEHATAN BAGI PENYANDANG DISABILITAS DI KABUPATEN SUKOHARJO - Agustinah, Pri; Astuti, Retno Sunu (Journal of Public Policy and Management Review, 2020)
Abstract Health insurance program for people with disabilities is a solution to solve problems faced by people with disabilities. Because they are vulnerable to disease and health costs are quite high with their low income. In the implementation, it was seen that there was a discrepancy in the recipient of the program, which should have been all covered, but in reality there were still persons with disabilities who had not received health insurance. The purpose of this study is to analyze the suitability of the program for disability in terms of benefits, and to know the obstacles in implementing the program. The research method uses descriptive qualitative methods and data collection techniques using informants taken purposively. Data analysis using the Triangulation Method. The results showed that the suitability of the program with the target group showed positive results in accordance with the needs of persons with disabilities, while the suitability of the program with the implementing organization showed less than optimal due to incomplete data collection and the suitability of the target group with the implementing organization showed the same thing, the conditions set still unclear. Constraints for implementing the program are still lacking in human resources and clarity of administrative procedures. The advice given by researchers is that the Social Service needs to improve the quality and quantity of human resources and evaluate the health insurance program for people with disabilities.